Examining the etiology and pregnancy outcomes of 152 critically ill pregnant patients in the Intensive Care Unit - Weiman Liu; Junyou Su; Sumei Wang (BMC Pregnancy and Childbirth)
Abstract Background Collaborative multidisciplinary approaches in obstetrics, particularly in conjunction with Intensive Care Units (ICUs), offer innovative treatment strategies for critically ill pregnant women. This study aimed to assess pregnancy outcomes and mortality in critically ill pregnant women in the Intensive Care Unit (ICU) and to provide valuable clinical insights for improving the management of obstetric emergency care, reducing maternal and neonatal adverse outcomes, and improving the level of obstetric care. Methods This study retrospectively included 152 critically ill pregnant women admitted to the ICU. They were grouped according to the main reason for ICU admission as well as the variety of diseases present at the time of admission. Then their clinical data were evaluated. Results The results showed that the main obstetric factors leading to ICU admission were pregnancy-related hypertensive disease, postpartum hemorrhage, and acute fatty liver of pregnancy; the non-obstetric factors included either pregnancy complicated by heart disease, sepsis, or malignant tumors. The maternal mortality rate was higher in the non-obstetric direct factor group than in the obstetric direct factor group (22.12% vs. 6.25%, p = 0.016). As for the pregnancy outcome, the cesarean section rate in the group affected by obstetric factors was significantly higher than that in the group affected by non-obstetric factors (p = 0.008). Furthermore, the incidence of pregnancy termination and induced abortion before 28 weeks in the group affected by non-obstetric factors was significantly higher than that in the group affected by obstetric factors (all p < 0.05). There was a statistically significant difference in mortality among the three groups of patients with different SOFA scores (p = 0.000), suggesting that the mortality of critically ill pregnant women with higher SOFA scores increased, making it a valuable tool for evaluating prognosis. Conclusion Non-obstetric factors were the primary contributors for ICU admission of expecting mothers. Therefore, utilizing modalities that successfully analyze these factors can aid in understanding the characteristics of critically ill pregnant women, and advancing perinatal healthcare technologies to reduce maternal mortality rates.